1980
DOI: 10.1148/radiology.136.1.7384488
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography in the diagnosis of aortic aneurysm dissection or traumatic injury.

Abstract: Thirty patients thought to have an atherosclerotic thoracic aneurysm or chronic aortic dissection were evaluated by computed tomography (CT) and the findings compared with those from conventional radiography, thoracic aortography, and surgery. In all cases, CT defined the lesion and correlated well with angiography. Staging of atherosclerotic aneurysms was possible, and CT also demonstrated the relationship between true and false lumina in aortic dissections; however, aortography was often necessary to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Although artifacts related to cardiac and aortic pulsation, beam hardening, and breathing challenged aortic assessment (192), early conventional CT was deemed useful in minimizing unnecessary angiography in patients with false-positive chest radiographs, enabling confirmation of the absence of injury in patients at low risk (193)(194)(195). However, with the introduction of spiral CT, the days of performing urgent direct aortic arteriography to assess aortic injury were numbered (187,196) (Fig 8).…”
Section: All-in-one Emergency Diagnosis and Triage For The Injuredmentioning
confidence: 99%
“…Although artifacts related to cardiac and aortic pulsation, beam hardening, and breathing challenged aortic assessment (192), early conventional CT was deemed useful in minimizing unnecessary angiography in patients with false-positive chest radiographs, enabling confirmation of the absence of injury in patients at low risk (193)(194)(195). However, with the introduction of spiral CT, the days of performing urgent direct aortic arteriography to assess aortic injury were numbered (187,196) (Fig 8).…”
Section: All-in-one Emergency Diagnosis and Triage For The Injuredmentioning
confidence: 99%
“…It has been suggested that mediastinal hematoma remote from the great vessels and attributable to sources other than the aorta, such as vertebral fractures, should decrease suspicion for aortic injury. 24 Egan et al 25 stated that CT is useful in excluding aortic injury in a stable patient with mediastinal widening that may be caused by other thoracic injuries. In the study by Ishikawa et al, 26 48 cases were positive for mediastinal hematoma on CT, 15 of which were due to fracture of a thoracic bony structure.…”
Section: Resultsmentioning
confidence: 99%
“…The [1][2][3][4]. In case 7, the septum had a "diamond" configuration measuring 28 mm at its maximum ( Fig.…”
Section: Resultsmentioning
confidence: 99%